SEMANTIC AND STRUCTURAL FEATURES OF THE VOCABULARY OF COLOUR DESIGNATION IN THE RUSSIAN LANGUAGE - Tashlanova Nigora Djurayevna (European Journal of Humanities and Educational Advancements, 2024)
This article delves deeply into the semantic and structural features characterizing the vocabulary of colour designation in the Russian language. Employing a comprehensive lens, the study explores significant trends in the investigation of colour meanings. Adopting a comparative approach, the research delves into evolutionary facets, psycholinguistic considerations, derivational processes, and cognitive dimensions that collectively contribute to the richness of colour semantics. The article uncovers the intricate interplay between linguistic, psychological, and cultural elements that shape the nuanced understanding of colours in the Russian linguistic context. Furthermore, the study addresses the dynamic nature of colour designation by emphasizing its comparative, evolutionary, psycholinguistic, derivational, and cognitive dimensions. By navigating through these various perspectives, this research aims to provide a thorough and insightful exploration of the semantic and structural intricacies inherent in the vocabulary of colour designation within the Russian language